Noble gas composition in rainwater and associated weather patterns. Issue 12 (21st June 2013) - Warrier, Rohit B.; Clara Castro, M.; Hall, Chris M.; Lohmann, Kyger C.
Abstract [1] This work represents the first comprehensive noble gas study in rainwater. It was carried out in southeast Michigan. Results show that all rainwater samples are in disequilibrium with surface conditions. Two noble gas patterns are identified. The first one, associated with low‐pressure systems, presence of fog and light rainfall, displays a relative Ar enrichment together with Ne, Kr, and Xe depletion. The second one, associated with the passage of frontal systems, displays a mass‐dependent depletion pattern. Precipitation is characterized by thunderstorms, heavy rainfall, and high cloud ceiling heights. A diffusion mass‐transfer model suggests that noble gas patterns originate from ice. Complete re‐equilibration with surface conditions should occur within hours. For the first time, this study establishes a direct correlation between the noble gas composition in rainwater and weather patterns and highlights their potential to identify timing and location of recharge in shallow aquifer systems where infiltration is rapid.